Description of the Molecular and Phenotypic Spectrum of Lesch-Nyhan Disease in Eight Chinese Patients - Li, Lu; Qiao, Xiaohui; Liu, Fei; Wang, Jingjing; Shen, Huijun; Fu, Haidong; Mao, Jian-Hua (Frontiers in Genetics, 2022)
Background: Lesch-Nyhan disease (LND) is a rare disorder involving pathogenic variants in the HPRT1 gene encoding the enzyme hypoxanthine-guanine phosphoribosyltransferase (HGPRT) that result in hyperuricemia, intellectual disability, dystonic movement disorder, and compulsive self-mutilation. The purpose of the present study was to characterize the genetic basis of LND and describe its phenotypic heterogeneity by identifying the variation in the HPRT1 gene in a cohort of Chinese LND patients. Results: The median age at diagnosis was 31 mo (interquartile range (IQR): 7–76 mo), and the initial manifestations were mainly head control weakness and motor development delay. The median age of self-mutilation behavior onset was 19 mo (IQR: 17–24 mo), and all patients were required to travel in a wheelchair and fall into the predicament of compulsive self-harm behavior. There were two patients whose blood uric acid levels were normal for their high urinary acid excretion fraction without taking uric acid-lowering drugs. Seven different pathogenic variants of the HPRT1 gene were identified among eight independent pedigrees, including four novel mutations [c.299 (exon 3) T > A; loss (exon: 6) 84 bp; c.277_281delATTGC; c.468_470delGAT]. The pathogenic variant sites were mainly concentrated in exon 3, and truncating mutations (including frameshift mutations and nonsense mutations) were the most common genetic variant types (5/7, 71.4%). Conclusion: The present study described the phenotypic and molecular spectrum of LND in eight Chinese families, including four novel mutations, which expands our understanding of LND.